2018
DOI: 10.1159/000490430
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab and Bevacizumab but Not Aflibercept Inhibit Proliferation of Primary Human Retinal Pigment Epithelium in vitro

Abstract: Aim: Treatment of exudative age-related macular degeneration by using vascular endothelial growth factor (VEGF) antagonists is the gold standard today. So far, several bioactive molecules have been approved for therapeutic use. In this study, we investigate the effects of ranibizumab (Lucentis®), bevacizumab (Avastin®), and aflibercept (Eylea®) on primary human retinal pigment epithelial (hRPE) cells in vitro. Methods: hRPE cells were prepared from donor eyes and cultured under standard culture conditions. Scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The research complies with the human research act (HRA) stating that small quantities of bodily substances removed in the course of transplantation may be anonymized for research purposes without consent (HRA chapter 5, paragraph 38, Switzerland). hpRPE were prepared from left and right eyes of 15 anonymized donors ( Table 1 ) as previously described [ 37 , 38 ]. Briefly, hpRPE cells were harvested from the eyecup after enzymatic digestion and centrifuged with 259× g at 4 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The research complies with the human research act (HRA) stating that small quantities of bodily substances removed in the course of transplantation may be anonymized for research purposes without consent (HRA chapter 5, paragraph 38, Switzerland). hpRPE were prepared from left and right eyes of 15 anonymized donors ( Table 1 ) as previously described [ 37 , 38 ]. Briefly, hpRPE cells were harvested from the eyecup after enzymatic digestion and centrifuged with 259× g at 4 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Our data indicate that the HaCaT cells were less affected by the treatment with Aflibercept compared with the effect produced by Bevacizumab. Parisi et al had similar results when they evaluated the effect on healthy cells, on primary human retinal pigment epithelium cells and on scleral fibroblasts [ 18 ]. Their data indicated that Bevacizumab decreased primary human retinal pigment epithelium cells and scleral fibroblasts proliferation more that Aflibercept [ 18 ].…”
Section: ⧉ Discussionmentioning
confidence: 91%